Novel oxindole derivatives prevent oxidative stress-induced cell death in mouse hippocampal HT22 cells. (June 2018) - Hirata, Yoko; Yamada, Chika; Ito, Yuki; Yamamoto, Shotaro; Nagase, Haruna; Oh-hashi, Kentaro; Kiuchi, Kazutoshi; Suzuki, Hiromi; Sawada, Makoto; Furuta, Kyoji
Abstract: The current medical and surgical therapies for neurodegenerative diseases such as Alzheimer's disease and Parkinson's disease offer symptomatic relief but do not provide a cure. Thus, small synthetic compounds that protect neuronal cells from degeneration are critically needed to prevent and treat these. Oxidative stress has been implicated in various pathophysiological conditions, including neurodegenerative diseases. In a search for neuroprotective agents against oxidative stress using the murine hippocampal HT22 cell line, we found a novel oxindole compound, GIF-0726-r, which prevented oxidative stress-induced cell death, including glutamate-induced oxytosis and erastin-induced ferroptosis. This compound also exerted a protective effect on tunicamycin-induced ER stress to a lesser extent but had no effect on campthothecin-, etoposide- or staurosporine-induced apoptosis. In addition, GIF-0726-r was also found to be effective after the occurrence of oxidative stress. GIF-0726-r was capable of inhibiting reactive oxygen species accumulation and Ca 2+ influx, a presumed executor in cell death, and was capable of activating the antioxidant response element, which is a cis -acting regulatory element in promoter regions of several genes encoding phase II detoxification enzymes and antioxidant proteins. These results suggest that GIF-0726-r is a low-molecular-weight compound that prevents neuronal cell death through attenuation of oxidative stress. Among the more than 200 derivatives of the GIF-0726-r synthesized, we identified the 11 most potent activators of the antioxidant response element and characterized their neuroprotective activity in HT22 cells. Graphical abstract: Highlights: Novel oxindole compounds prevent oxidative stress-induced cell death. The lead compound GIF-0726-r inhibits ROS accumulation and Ca 2+ influx. GIF-2165X-G1, obtained by chemical modification of GIF-0726-r, is a potent ARE inducer.